Intimate Partner Violence and Depression Screening of Mothers with Infants in the Neonatal Intensive Care Unit - Desai, Sujata; Stanzo, Karen; Benskin, Beverley; Cardenas, Kristina; Gilkey, Tiffany W.; Chiruvolu, Arpitha (American Journal of Perinatology, 2024)
Objective This study aimed to determine the prevalence of partner violence and depression in neonatal intensive care unit (NICU) mothers.Study Design This was a descriptive study. Mothers were screened in a safe room away from their partner with the Edinburgh Postnatal Depression Scale (EPDS) and the Abuse Assessment Screen Tool (AAS) within 2 days of the newborn's admission. The EPDS was administered again 2 weeks later and then at discharge.Results Nearly 20% of mothers reported on the AAS that they had experienced physical abuse since pregnancy. Abuse significantly predicted baseline depression 48 hours after delivery. A significant relationship emerged between depression and past year partner violence, with 100% experiencing abuse in the past year after pregnancy. Regular hospital intake questions underreported NICU mothers' partner violence experience and feelings of depression.Conclusion There was a marked difference between what mothers reported in their health history at admission versus evidence-based surveys in a private setting. These results challenge assumptions that accurate screening happens at hospital admission. It is imperative to use evidence-based scales after delivery to improve outcomes.Key Points
Keywords: partner violence; postpartum depression; NICU mothers; abuse and depression screening